In the presence of god : does acceptance by god increase prosocial behavior? - Woo, Yue Ting (2019)
Many people believe in God, but they may not mentally represent God in the same way. Though the “anthropomorphism of God” has usually been taken to mean the ascribing of human traits and qualities to God, this paper puts forth the perspective that the way people think about their own relationship with God is also guided by social judgement. Further, I argue that because relationships with God are based on the same foundations as that with other humans, perceiving a loving and accepting relationship with God can prime people to expect a similar experience with people. Hence, I hypothesized that reminders and thoughts about being accepted by God would result in more positive expectations towards a partner in a Dictator Game than thinking about being rejected by God. Further, I predicted that participants’ expectations would affect their own willingness to be prosocial in the Dictator Game. Results from two experimental studies did not support the first hypothesis, though participants’ expectations of their partner was consistently found to be a significant predictor of their own prosociality. Four possibilities for the null findings are discussed and recommendations for future studies are made.